Early embryonic death in mares: clinical and hormonal aspects - Papa, Frederico Ozanam [UNESP]; Lopes, Maria Denise [UNESP]; Alvarenga, Marco Antonio [UNESP]; Meira, Cezinande de [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Langoni, Hélio [UNESP]; Ribeiro, Erley Felix [UNESP]; Azedo, Antonio Esteves [UNESP]; Bomfim, Antonio Carlos de Miranda [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 1998)
O presente estudo objetivou diagnosticar as causas da morte embrionária precoce em 128 éguas. Amostras de soro foram coletadas nos dias 4, 7, 10, 13, 16, 19, 21 e 30 após ovulação, para dosagens hormonais e mensurações do corpo lúteo. O diâmetro e as características da vesícula embrionária foram avaliados, através da ultra-sonografia, a partir do 12º dia pós-ovulação. Das 128 éguas estudadas, 17 (13.28%) apresentaram morte embrionária. O diâmetro do corpo lúteo, bem como as concentrações plasmáticas de progesterona, foi semelhante nos grupos que apresentaram morte embrionária e nos que mantiveram a gestação. Os níveis de estrogeno plasmático foram mais elevados no grupo das fêmeas que mantiveram a gestação. Os exames citológicos, microbiológicos e histopatológicos revelaram que a maioria das éguas com diagnóstico de morte embrionária eram portadoras de endometrites.

The present study aimed to diagnose early embryonic death in 128 mares. Blood samples were collected at the 4th, 7th, 10th, 13th, 16th, 19th, 21st and 30th day after ovulation and the diameter of the corpus luteum was measured. The diameter and characteristics of the embryonic vesicle were evaluated by ultrasonography. Microbiology, cytology and histopathology were carried out in mares with embryonic death. Plasma oestrogen and progesterone concentration were measured by radioimmunoassay. From 128 mares, 17 (13.28%) showed early embryonic death. The embryonic losses took place at 19 days of pregnancy in 47.05% and at 21 days of pregnancy in 29.4% of the mares. The diameter of the corpus luteum in the mares that maintained pregnancy was similar to those with embryonic loss. Otherwise, the diameter of the embryonic vesicles was bigger at the 16th, 19th, 21st and 30th day of pregnancy when compared to the mares with embryonic loss. The mean plasma progesterone concentration was similar in both groups and the median plasma oestrogen concentration was higher in the pregnant mares. The cytological, microbiological and histopathological exams revealed that most of the mares had endometritis. Ultrasonography provided an early diagnosis of pregnancy (from the 12th day post-ovulation) and important information about the development of embryo and embryonic death. Endometritis was considered the main cause of embryonic losses in this study.
Morte embrionária precoce em éguas: aspectos clínicos e hormonais
Keywords: Mortalidade embrionária; Progesterona; Estrógeno; Histopatologia; Éguas; Embryo mortality; Progesterone; Estrogen; Histopathology; Equine